Acute cyclosporine overdose: A systematic review - Ali Ershad; Shohreh Taziki; Melika Ebrahimian; Sahel Shafiee Dolat Abadi (Medicina Clínica Práctica, 2023)
Context: Cyclosporine is the first drug to revolutionize organ transplantation; this drug was approved for autoimmune and graft versus host disease (GVHD) treatment. Based on case reports, Cyclosporine overdose has morbidities (including acute renal failure (ARF), seizure, coma, hepatitis, and neurologic disorder) and mortality. Background: Although cyclosporine was discovered many years ago and is still used to treat many diseases, its narrow therapeutic index can cause significant problems. Methods: We performed a literature search across three databases, including Medline, EMBASE, and Science Direct, and reviewed statistical sources from January 1, 1983, to April 31, 2020. Papers were eligible for what they described, either acute or acute chronic cyclosporine overdose. At least one serum cyclosporine concentration had to be reported for inclusion. Reports on chronic poisoning, studies on side effects of therapeutic drug uses, and animal studies were excluded. Results: We found 81 cases from 37 articles that met inclusion criteria, potentially life-treating symptom coma (10%), seizure (16%), cardiac tachycardia (3%), and death (5%). Pediatrics are more susceptible to cyclosporine overdose, treatment interventions like gastric lavage (6.3%), charcoal administration (6.3%), whole blood exchange (5%), a huge overdose of more than 400 mg/kg oral route, or serum levels of more than > 3800 ng/ml related to death, seizure associated with upper threshold level > 500 ng/ml and coma related to the upper level of 1000 ng/ml cyclosporine levels, charcoal administration, and whole blood exchange reduce cyclosporine level and cure the patients. Conclusions: Fifty percent of patients showed no or minimum toxicity and fifty percent showed severe signs and symptoms of poisoning. Almost all patients have a good outcome if cyclosporine overdose is diagnosed and treated on time. Resumen: Contexto: La ciclosporina es el primer fármaco que revolucionó el trasplante de órganos; este fármaco está aprobado para el tratamiento de la enfermedad autoinmune y de injerto contra huésped (EICH). Según los informes de casos, la sobredosis de ciclosporina tiene morbilidades (que incluyen insuficiencia renal aguda (IRA), convulsiones, coma, hepatitis y trastornos neurológicos) y mortalidad. Antecedentes: Aunque la ciclosporina se descubrió hace muchos años y todavía se usa para tratar muchas enfermedades, su estrecho índice terapéutico puede causar problemas importantes. Métodos: Realizamos una búsqueda bibliográfica en tres bases de datos, incluidas Medline, EMBASE y Science Direct, y revisamos fuentes estadísticas desde el 1 de enero de 1983 hasta el 31 de abril de 2020. Los artículos eran elegibles por lo que describían, sobredosis de ciclosporina aguda o crónica aguda. Se tuvo que informar al menos una concentración de ciclosporina sérica para su inclusión. Se excluyeron los informes sobre intoxicaciones crónicas, los estudios sobre los efectos secundarios del uso de fármacos terapéuticos y los estudios con animales. Resultados: Encontramos 81 casos de 37 artículos que cumplían con los criterios de inclusión, coma sintomático de tratamiento potencialmente vital (10 %), convulsiones (16 %), taquicardia cardíaca (3 %) y muerte (5 %). Los pediátricos son más susceptibles a la sobredosis de ciclosporina, las intervenciones de tratamiento como el lavado gástrico (6,3 %), la administración de carbón (5 %), el intercambio de sangre total (5 %), una sobredosis enorme de más de 400 mg/kg por vía oral o los niveles séricos de más de > 3800 ng/ml relacionado con la muerte, convulsiones asociadas con el nivel de umbral superior > 500 ng/ml y coma relacionado con el nivel superior de 1000 ng/ml niveles de ciclosporina, administración de carbón y recambio de sangre total reducen el nivel de ciclosporina y curan el paciente. Conclusiones: El 50% de los pacientes presentó toxicidad nula o mínima y el 50% presentó signos y síntomas severos de intoxicación. Casi todos los pacientes tienen un buen resultado si la sobredosis de ciclosporina se diagnostica y trata a tiempo.